Avaliação da autozigosidade em vacas Nelore (Bos indicus) através de genótipos SNP de alta densidade - Zavarez, Ludmilla Balbo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The current beef cattle chain has had significant help of animal breeding programs to its success. The development of different methods to perform phenotypic and genotypic evaluation has the objective of selecting flocks and producing genetically superior animals with standardized production. The productive standardization of a herd must be the result of directed matings, which can lead to increased incidence of homozygous alleles in the genome of animals. The increase of autozygosity in the population, i.e., increasing the number of animals with alleles identical by descent (IBD), is derived from the mating of related individuals. In this context, the most robust tool to identifies the animal's genome fragments that are identical by descent is the estimation of the inbreeding coefficient based on runs of homozygosity (ROH), which is called (FROH). Evolutionary events, such as the process of natural selection, random or genetic drift, and population bottleneck, may have contributed towards increasing the autozygosity and occurrence of IBD alleles in the genome of a population resulting crosses of related individuals. This thesis reviewed the state of the art with respect to the study of inbreeding determined by genomic analysis (Chapter 1), and applied this knowledge in the analysis of the distribution of autozygosity levels based on runs of homozygosity (ROH) in 1,278 Nelore females genotyped to more than 777,000 SNPs, and identified autozygote regions possibly associated with natural selection, domestication, fertility, evolution and adaptation of cattle (Chapter 2). This study open prospects for conducting detailed analysis on the influence of genomic autozygosity caused by selective pressure on specific alleles in Nelore cattle

A pecuária bovina de corte da atualidade conta com o auxílio significativo dos programas de melhoramento genético animal para seu sucesso. O desenvolvimento de distintos métodos para realizar avaliações fenotípicas e genotípicas, tem o intuito de selecionar os rebanhos e obter animais geneticamente superiores com produção padronizada. A padronização produtiva de um rebanho deve ser resultante de acasalamentos dirigidos, que podem levar ao aumento da ocorrência de alelos homozigotos no genoma dos animais. Esse aumento da autozigosidade na população, isto é, o aumento do número de animais com alelos idênticos por descendência (IBD), provém do acasalamento entre indivíduos aparentados. Nesse contexto, a ferramenta mais robusta para identificar os fragmentos do genoma animal que são idênticos por descendência é a estimação do coeficiente de endogamia baseado nas corridas de homozigosidade (ROH), que é denominado (FROH). Eventos evolutivos, tais como: o processo de seleção natural, a deriva genética ou aleatória, e o gargalo populacional, podem ter contribuído com o aumento da autozigosidade e da ocorrência de alelos IBD no genoma de uma população resultante da reprodução entre indivíduos aparentados. Essa dissertação revisou o estado da arte do que concerne o estudo da endogamia determinada por análises genômicas (Capítulo 1), e aplicou tais conhecimentos na análise da distribuição dos níveis de autozigosidade baseado em corridas de homozigosidade (ROH) em 1.278 fêmeas da raça Nelore genotipadas para mais de 777 mil SNPs, e identificou regiões autozigotas possivelmente associadas à seleção natural, domesticação, fertilidade, evolução e adaptação dos bovinos (Capítulo 2). O presente estudo abre perspectivas para a realização de análises detalhadas que permitam a mensuração da influência da autozigosidade genômica causada pela pressão seletiva sobre alelos específicos em bovinos ...
Keywords: Bovino; Nelore (Zebu); Domesticação; Endogamia; Genômica; Inbreeding